Analysis of Conceptual, Factual, Principle, and Skill Errors Based on Students' Thinking Ability: How is it Connected to Science Learning? - Mufidah Mufidah; Niluh Sadiani; Akina Akina; Nuraini Nuraini; Khairunnisa Khairunnisa (Postgraduate, University of Mataram, 2023)
This study aims to describe misconceptions about concepts, facts, principles and skills based on thinking skills that were made by fifth grade students at SD Inpres 6 Lolu in solving multiplication fraction problems. This research is descriptive qualitative research which is based on the problem solving steps put forward by Polya. The research subjects were taken by 6 students based on the level of thinking skills determined using the Standard Deviation (SD) calculation. Data collection methods used are test and interview methods. The study's findings reveal that students make different types of errors based on their thinking ability in the process of solving mathematical problems. These errors can be categorized into four main areas namely: factual errors, conceptual errors, skill errors, principal errors. In summary, the study highlights that students' thinking ability is closely linked to the types of errors they make when solving mathematical problems. These errors primarily involve faulty facts, conceptual misunderstandings, skill-related issues, and principal errors. Understanding these patterns of errors can guide educators in developing targeted interventions to improve students' mathematical problem-solving skills